Applications of various iris retractors - Wilczyński, Michał; Omulecki, Wojciech (Klinika Oczna / Acta Ophthalmologica Polonica, 2012)
Fast development of ophthalmology which can be observed in the recent years, is connected with the development of modern technology used in the diagnostics and treatment of ocular diseases. Eyes with a narrow pupil, which doesn’t respond to standard pharmacologic management applied preoperatively, are a challenge for any ophthalmic surgeon. The purpose of the study is to describe various surgical devices used for achieving adequate intraoperative pupillary diameter in cataract patients who for various reasons do not respond to pharmacologic mydriasis.